Interactive Media Development “Sing: Listen And Speak” Based on Acoustic Music For Language Introduction for Children Aged (5-6) Years in Kindergarten - Luthfi, Tasyfiah Aliya; Sumarni, Sri; Safitri, Erna Retna (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Language learning in early childhood still faces obstacles in the form of limited interactive media that are appropriate to the characteristics of child development, especially in integrating auditory, visual, and linguistic aspects in an integrated manner. The use of existing digital songs tends to not pay attention to child-friendly musical elements and is not directed at strengthening thematic vocabulary. This study aims to develop an interactive media "Sing: Listen and Speak" based on acoustic music to improve the language recognition skills of children aged 5-6 years in kindergarten. The research method uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation, with data collection techniques in the form of interviews, questionnaires, observations, and tests. The research subjects were students and educators at Pembina 5 State Kindergarten, Palembang. The results showed that the developed media has a very high level of validity based on the assessment of media, material, and language experts. The media was also declared practical to use by teachers and interesting to students based on the results of the practicality test. In addition, the media proved effective in improving children's language skills, indicated by an increase in posttest scores compared to pretests with a medium to high N-Gain category. In conclusion, the interactive media “Sing: Listen and Speak” based on acoustic music is effective, valid, and practical as an innovation in early childhood language learning that is able to increase engagement, memory, and vocabulary mastery in a fun and meaningful way.